A novel multistage antigens ERA005f confer protection against Mycobacterium tuberculosis by driving Th-1 and Th-17 type T cell immune responses - Fan, Xueting; Zhao, Xiuqin; Wang, Ruibai; Li, Machao; Luan, Xiuli; Wang, Ruihuan; Wan, Kanglin; Liu, Haican (Frontiers in Immunology, 2023)
Introduction Tuberculosis (TB) is a major threat to human health. In 2021, TB was the second leading cause of death after COVID-19 among infectious diseases. The Bacillus Calmette–Guérin vaccine (BCG), the only licensed TB vaccine, is ineffective against adult TB. Therefore, there is an urgent need to develop new effective vaccines. Methods In this study, we developed a novel multistage subunit vaccine (ERA005f) comprising various proteins expressed in metabolic states, based on three immunodominant antigens (ESAT-6, Rv2628, and Ag85B). We utilized the E. coli prokaryotic expression system to express ERA005f and subsequently purified the protein using nickel affinity chromatography and anion exchange. Immunogenicity and protective efficacy of ERA005f and ERA005m were evaluated in BALB/c mice. Results ERA005f was consistently expressed as an inclusion body in a prokaryotic expression system, and a highly pure form of the protein was successfully obtained. Both ERA005f and ERA005m significantly improved IgG titers in the serum. In addition, mice immunized with ERA005f and ERA005m generated higher titers of antigen-specific IgG2a than the other groups. Elispot results showed that, compared with other groups, ERA005f increased the numbers of IFN-γ-secreting and IL-4-secreting T cells, especially the number of IFN-γ-secreting T cells. Meanwhile, ERA005f induced a higher number of IFN-γ+ T lymphocytes than ERA005m did. In addition, ERA005f improved the expression of cytokines, including IFN-γ, IL-12p70, TNF-α, IL-17, and GM-CSF and so on. Importantly, both ERA005f and ERA005m significantly inhibited the growth of Mtb. Conclusion The novel multistage antigen ERA005f elicited a strong antigen-specific humoral response and Th-1 and Th-17 cell-mediated immunity in mice. Meanwhile, it can effectively inhibit H37Rv growth in vitro, and represents a correlate of protection in vivo, indicating that ERA005f may exhibit excellent protective efficacy against Mycobacterium tuberculosis H37Rv infection. Our study suggests that ERA005f has the potential to be a promising multistage tuberculosis vaccine candidate.